Eosinophil Activation by Toll-Like Receptor 4 Ligands Regulates Macrophage Polarization - Yoon, Jiyoung; Um, Han-Na; Jang, Jinsun; Bae, Young-An; Park, Woo-Jae; Kim, Hee Joo; Yoon, Mee-Sup; Chung, Il Yup; Jung, YunJae (Frontiers in Cell and Developmental Biology, 2019)
Eosinophils are terminally differentiated granulocytes that have long been considered as destructive cells associated with Th2 type immune responses such as allergic inflammation and helminth infections. Recently, eosinophils have been actively studied as multifunctional leukocytes regulating an array of physiological responses through interaction with other immune cells. In this study, we examined the expression and function of Toll-like receptors (TLRs) in eosinophilic EoL-1 cells and demonstrated the expression of a number of immune mediators in activated EoL-1 cells and their interaction with the macrophage cell line THP-1 upon TLR4 ligand stimulation. EoL-1 cells differentiated with butyrate increased expression of TLR3, TLR4 and TLR7 at mRNA and protein level. Mature eosinophils derived from human cord blood CD34+ cells also showed the expression of a panel of TLR transcripts and TLR4 was the most highly expressed TLR. Among the cognate ligands of TLR3, TLR4, and TLR7, lipopolysaccharide or palmitic acid significantly increased mRNA expression of immune mediators in differentiated EoL-1 cells. Notably, palmitic acid-treated differentiated EoL-1 cells showed significantly up-regulated expression of Th2 type cytokines and transcription factors driving eosinophil differentiation. To evaluate functional significance of TLR4 ligand- stimulated eosinophils, we added conditioned media from EoL-1 cells to differentiated THP-1 cells and assessed the expression of M1 macrophage or M2 macrophage-related markers. M1 and M2 macrophage markers were significantly upregulated by conditioned media from lipopolysaccharide and palmitic acid stimulated EoL-1 cells, respectively. In addition, the adipose tissue of obese mice, where eosinophils are decreased due to obesity-induced inflammation, showed significantly decreased frequency of M2 macrophages, despite an increase in the total macrophage numbers. Based on these collective data, we proposed that eosinophils regulate macrophage polarization through functional changes induced by different TLR4 ligands.